A New Crystal Form of the SARS-CoV-2 Receptor Binding Domain: CR3022 Complex—An Ideal Target for In-Crystal Fragment Screening of the ACE2 Binding Site Surface - Nichols, Charlie; Ng, Joseph; Keshu, Annika; Fraternali, Franca; De Nicola, Gian F. (Frontiers in Pharmacology, 2020)
In-crystal fragment screening is a powerful tool to chemically probe the surfaces used by proteins to interact, and identify the chemical space worth exploring to design protein-protein inhibitors. A crucial prerequisite is the identification of a crystal form where the target area is exposed and accessible to be probed by fragments. Here we report a crystal form of the SARS-CoV-2 Receptor Binding Domain in complex with the CR3022 antibody where the ACE2 binding site on the Receptor Binding Domain is exposed and accessible. This crystal form of the complex is a valuable tool to develop antiviral molecules that could act by blocking the virus entry in cells.